Slag uses in making an ecofriendly and sustainable concrete: A review - Amran, M. (Elsevier Ltd, 2021)
A single ton of ordinary Portland cement (OPC) demands around 4.0 G Joule energy and creates about a ton of CO2 emission. As part of our effort to preserve the environment, the incorporation of ground granulated blast-furnace slag (GGBFS) or fully replaced by alkali-activated slag (AAS) as an alternative binder to OPC. This concrete is environmental-friendly and also eases concerns in energy usage, raw material, and manufacturing cost for the traditional concrete. The cementitious properties of GGBFS and AAS promote their usage in the concrete matrix. Partial inclusion of slag for cement produces OPC or fully replaced by AAS is getting more attention as it is more pumpable, chemically stable, and resistant to an aggressive environment. This paper reviews the source, clean production and chemical compositions of the GGBFS and AAS. This literature review also objects to provide reviews on the properties, hardening conditions, and behaviors of GGBFS and AAS -based concrete composites as well as to synopsize the research development trends to generate comprehensive insights into the potential applications of GGBFS and AAS concrete as raw building materials for making sustainable and greener concrete composites, towards industrializing ecofriendly buildings today. Â© 2020 Elsevier Ltd